Treatment performance evaluation of conventional Fenton process and electro-Fenton process using two different electro-Fenton reactors for aniline degradation - Pagaling, Eric D. (2006)
Aniline degradation was investigated using the conventional Fenton (CF) process and eletro-Fenton (EF) process employing the plate type electrode and rod type electrode EF reactors with Ir02/RuO2 coated titanium metal anodes and stainless steel cathodes. The treatment performance evaluation of the two EF reactors was conducted by determining the effects H2O2, Fe2+, electric current and initial aniline concentration on the aniline and COD removal efficiencies, initial aniline degradation rates, kinetic models, H2O2 efficiency and power consumption for aniline and COD removal. Aside from this the change in the BOD, toxicity and oxalic acid production of a high initial aniline concentration having 10,000ppm COD was also studied using the two EF reactors.
The EF process was superior to the CF process due to its higher treatment efficiency at low Fe2+ concentrations, low inorganic sludge production and low residual H2O2 after treatment. Both of the EF reactors have the same aniline and COD removal efficiencies at high H2O2 concentrations however at H2O2 concentrations lower than 58mM, the plate type electrode EF reactor was superior to the rod type electrode EF reactor. An increase in H2O2 and Fe2+ concentrations lowered power consumptions for aniline and COD removal for both of the EF reactors. However increase in H2O2 greater than 58mM and Fe2+ greater than 1.61 mM had no further effect on power consumption due to decreased niline and COD removal efficiencies. The rod type electrode EF reactor consumes twice as much power for aniline and COD removal than the plate type electrode EF reactor and that COD removal requires twice as much power than aniline removal. Increase in applied electric current increases the differences in the power consumption between the rod type electrode and plate type electrode EF reactors from 1.7 to 3.3 times. Treatment of high concentration aniline solution resulted into an increased BOD and showed lowered toxicity values of 0.18 and 0.25 for the plate type electrode and rod type electrode EF reactors respectively. The plate type electrode EF reactor was found to be more versatile than rod type electrode EF reactor since it can be operated at different Fe2+ concentrations and at higher electric current applications.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Electrolytic oxidation; Aniline; Fenton's reagent